2014
DOI: 10.1002/2014ja020208
|View full text |Cite
|
Sign up to set email alerts
|

The role of ion‐molecule reactions in the growth of heavy ions in Titan's ionosphere

Abstract: The Ion and Neutral Mass Spectrometer (INMS) and Cassini Plasma Spectrometer (CAPS) have observed Titan's ionospheric composition and structure over several targeted flybys. In this work we study the altitude profiles of the heavy ion population observed by the Cassini Plasma Spectrometer-Ion Beam Spectrometer (CAPS-IBS) during the nightside T57 flyby. We produce altitude profiles of heavy ions from the C6-C13 group (C i indicates the number, i, of heavy atoms in the molecule) using a CAPS-IBS/INMS cross calib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 45 publications
3
35
0
Order By: Relevance
“…This technique has been previously used at Titan (Coates et al, ; Crary et al, ; Desai et al, ) and at Enceladus (Coates et al, ; Hill et al, ; Jones et al, ). The along‐track ion velocity term v i has not previously been accounted for at Enceladus but has been accounted for at Titan (Crary et al, ; Westlake et al, ), the addition of this term is explained in section .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This technique has been previously used at Titan (Coates et al, ; Crary et al, ; Desai et al, ) and at Enceladus (Coates et al, ; Hill et al, ; Jones et al, ). The along‐track ion velocity term v i has not previously been accounted for at Enceladus but has been accounted for at Titan (Crary et al, ; Westlake et al, ), the addition of this term is explained in section .…”
Section: Methodsmentioning
confidence: 99%
“…CAPS Ion Beam Spectrometer (IBS) data have been previously used to study the composition of Titan's atmosphere, reinforcing arguments on hydrocarbon detections made by INMS in addition to creating composition altitude profiles and quantifying their abundance (Crary et al, ; Westlake et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…3) Large negative ions with masses greater than 5000 u measured by the CAPS Electron Spectrometer (ELS; panel C) that increase in complexity at altitudes below 1000 km . Westlake et al (2014) demonstrated with correlation analysis that the molecular growth between ions and neutral species below 200 u appears to take place in large part due to addition reactions of C 2 compounds (C 2 H 2 and C 2 H 4 ). Westlake et al (2014), Waite et al (2006), and Lavvas et al…”
Section: Reactions In the Higher Layers Of Titan's Atmosphere And Ionmentioning
confidence: 98%
“…Currently formation of complex molecules, ions, and haze is poorly constrained. The present lack of constraints on the aerosol chemical composition precludes clear benchmarks for further synthetic organic solids studies in the laboratory (Cable et al, 2012;Gautier et al, 2014;Sebree et al, 2014;Westlake et al, 2014). A mission dedicated to Titan is essential to determine haze composition, how its formation in the ionosphere links to other levels, if its composition changes with altitude, how it affects climate, and its role in the methane cycle and surface composition, morphology and alteration.…”
Section: Complex Chemistry and Haze Formationmentioning
confidence: 99%